Numerical study of perforated obstacles effects on the performance of solar parabolic trough collector - Fahim, Tayeb; Laouedj, Samir; Abderrahmane, Aissa; Driss, Zied; Tag-ElDin, El Sayed Mohamed; Guedri, Kamel; Younis, Obai (Frontiers in Chemistry, 2023)
Improving heat transfer in the receiver of a parabolic-trough solar collector (PTSC) is numeri-cally studied by introducing perforated obstacles. While the proposed approach to improve the collector's performance is promising, the use of barriers results in increased pressure loss. Based on using the renormalization-group (RNG) k-ɛ turbulent model associated with standard wall function, the thermo-hydraulic analysis is conducted by using Thermal oil D12 as working fluid. Firstly, a comparison study against a receiver without perforated barriers is discussed. Sec-ondly, the receiver tube with perforated obstacles is taken for various configurations and Reynolds number range ([18,860 - 81,728]). The results show that this receiver tube with three holes (PO3) showed better heat transfer characteristics. In addition, the Nusselt number (Nu) increases about 115% with the increase of friction factor 5 to 6.5 times and the performance evaluation criteria (PEC) changes from 1.22 to 1.24. The temperature of thermal oil fluid attains its maximum value at the exit, and higher temperatures (462.1 K) are found in the absorber tube with perforated obstacles with three holes (PO3). Therefore, using the use of a perforated obstacles receiver for parabolic trough concentrator is highly recommended when a significant improvement in system performance is achieved